Wall shear stress measured by phase contrast cardiovascular magnetic resonance in children and adolescents with pulmonary arterial hypertension - Truong, Uyen (BioMed Central, 2013)
BACKGROUND: Pulmonary arterial hypertension (PAH) is a devastating disease with significant morbidity and mortality. At the macroscopic level, disease progression is observed as a complex interplay between mean pulmonary artery pressure, pulmonary vascular resistance, pulmonary vascular stiffness, arterial size, and flow. Wall shear stress (WSS) is known to mediate or be dependent on a number of these factors. Given that WSS is known to promote architectural vessel remodeling, it is imperative that the changes of this factor be quantified in the presence of PAH. METHODS: In this study, we analyzed phase contrast imaging of the right pulmonary artery derived from cardiovascular magnetic resonance to quantify the local, temporal and circumferentially averaged WSS of a PAH population and a pediatric control population. In addition, information about flow and relative area change were derived. RESULTS: Although the normotensive and PAH shear waveform exhibited a WSS profile which is uniform in magnitude and direction along the vessel circumference at systole, time-averaged WSS (2.2 ± 1.6 vs. 6.6 ± 3.4 dynes/cm(2), P = 0.018) and systolic WSS (8.2 ± 5.0 v. 20.0 ± 9.1 dynes/cm(2), P = 0.018) was significantly depressed in the PAH population as compared to the controls. BSA-indexed PA diameter was significantly larger in the PAH population (1.5 ± 0.4 vs. 0.7 ± 0.1 cm/m(2), P = 0.003). CONCLUSIONS: In the presence of preserved flow rates through a large PAH pulmonary artery, WSS is significantly decreased. This may have implications for proximal pulmonary artery remodeling and cellular function in the progression of PAH.